Persistent Racial and Sex Disparities in Outcomes After Coronary Artery Bypass Surgery: A Retrospective Clinical Registry Review in the Drug-eluting Stent Era. Issue 4 (October 2020) - Enumah, Zachary Obinna; Canner, Joseph K.; Alejo, Diane; Warren, Daniel S.; Zhou, Xun; Yenokyan, Gayane; Matthew, Thomas; Lawton, Jennifer S.; Higgins, Robert S. D.
Abstract : Objective: The purpose of this study was to assess the temporal trends in 30-day mortality by race group for patients undergoing coronary artery bypass grafting (CABG) between 2011 and 2018 and to investigate the effect of race and sex on postoperative outcomes after CABG. Summary Background Data: Cardiovascular diseases remain a leading cause of death in the United States with studies demonstrating increased morbidity and mortality for black and female patients undergoing surgery. In the post drug-eluting stent era, studies of racial disparities CABG are outdated. Methods: We performed a retrospective analysis of the Society for Thoracic Surgeons database for patients undergoing CABG between 2011 and 2018. Primary outcome was 30-day mortality. Secondary outcomes included postoperative length of stay, surgical site infection, sepsis, pneumonia, stroke, reoperation, reintervention, early extubation, and readmission. Results: The study population was comprised of 1, 042, 506 patients who underwent isolated CABG between 2011 and 2018. Among all races, Black patients had higher rates of preoperative comorbidities. Compared with White patients, Black patients had higher overall mortality (2.76% vs 2.19%, P < 0.001). On univariable regression, Black patients had higher rates of death, infection, pneumonia, and postoperative stroke compared to White patients. On multivariable regression, Black patients had higher odds of 30-day mortality compared to white patients [odds ratio (OR) = 1.11, 95% confidence interval (CI) 1.05–1.18]. Similarly, female patients had higher odds of death compared to males (OR = 1.26, 95% CI 1.21–1.30). Conclusions: In the modern era, racial and sex disparities in mortality and postoperative morbidity after coronary bypass surgery persist with Black patients and female patients consistently experiencing worse outcomes than White male patients. Although there may be unknown or underappreciated biological mechanisms at play, future research should focus on socioeconomic, cultural, and multilevel factors.